Microbiota under bloom stress: A review and meta-analysis of bloom-associated cyanopeptides, environmental stressors, and microbial shifts in free-living and host gut microbiomes - Mathias Ahii Chia; Adriana Sturion Lorenzi; Micheline Kézia Cordeiro-Araújo; Suleiman Dauda; Zainab Abdullahi; Regina Anya Otogo; Zubeidat Precious Ahmed; Elizabeth Abdulmalik; Maria Onma Onaji; Maria do Carmo Bittencourt-Oliveira; Viviane Moschini Carlos; Triantafyllos Kaloudis; et al. (Science of The Total Environment, 2026)

Effect of ultraviolet radiation (type B) and titanium dioxide nanoparticles on Microcystis aeruginosa and Lemna minor growth rate and potential allelopathic interactions - Sadiya Awala Samuel; Suleiman Dauda; Regina Anya Otogo; Adriana Sturion Lorenzi; Zainab Abdullahi Ibrahim; Elizabeth Abdulmalik; Micheline Kezia Cordeiro-Araujo; Mathias Ahii Chia (Aquatic Ecology, 2026)

Interactive effects of ivermectin and nitrogen levels on phytoplankton biomass and stress responses - Suleiman Dauda; Adriana Sturion Lorenzi; Maria Onma Onaji; Micheline Kézia Cordeiro-Araújo; Yusuf Okpanachi Ibrahim; Kala Musa Adamu; Idris Aisha Adam; Mariya Awwal Likoro; Mathias Ahii Chia (Ecotoxicology, 2026)
Ivermectin (IV), a commonly used antiparasitic drug for livestock and humans, eventually finds its way into aquatic environments, primarily through fecal matter and livestock carcasses. The presence of IV in water bodies may pose a risk to non-target aquatic organisms, such as phytoplankton, whose primary habitat is the aquatic environment. The adverse effects of IV may be exacerbated by its interactions with organic matter and nutrients, such as nitrogen, in aquatic ecosystems. Here, the combined effects of IV with low and replete nitrogen on the biomass and oxidative stress responses of Chlorella vulgaris , Selenastrum capricornutum , and Microcystis flos-aquae were studied. Additionally, the microcystins production of M. flos-aquae under the treatment conditions was also measured. The results show that the interaction between IV and nitrogen levels mostly did not affect the biomass of C. vulgaris , S. capricornutum , and M. flos-aquae . IV interacted with replete nitrogen to increase oxidative stress parameters, and also stimulated the three species to produce higher cell densities. Similarly, the interaction between IV and low nitrogen stressed M. flos-aquae and increased its production of microcystins (MC). These findings provide valuable insights into the complex interactions between IV, nitrogen levels, and phytoplankton physiology, highlighting the adaptive mechanisms used by phytoplankton in response to these conditions.

Impact of perfluorooctanesulfonic acid (PFOS) on phytoplankton community and physiological responses - Suleiman Dauda; Yillek Simon Gotan; Sadiya Awala Samuel; Adriana Sturion Lorenzi; Zainab Abdullahi Ibrahim; Dora Nguemo Iortsuun; Mathias Ahii Chia (Aquatic Ecology, 2026)
Perfluorooctanesulfonic acid (PFOS), a persistent and bioaccumulative substance, has emerged as a major environmental contaminant of global concern. PFOS, widely used in industry and consumer products, is common in aquatic ecosystems and may harm primary producers like phytoplankton, though its effects on their community structure and physiology remain unclear. Here, we investigated the impact of PFOS on freshwater physicochemical parameters, phytoplankton community dynamics, biochemical composition, and oxidative stress responses in a mesocosm experiment over a 28-day period. The water quality indicators generally were unaltered by PFOS exposure, but phosphate levels decreased initially in the control. Phytoplankton biomass (cell density) decreased at 10 µg L −1 and 10 mg L −1 PFOS exposures. Phytoplankton species richness, Shannon, and Simpson diversity indices declined at 10 mg L −1 , with communities at this concentration becoming distinctly different from the control and lower PFOS treatments by day 28. This shift in community structure was primarily driven by taxa such as Chlorogonium sp. and Microcystis aeruginosa , which contributed strongly to the observed compositional dissimilarity. Proteins content in the phytoplankton increased under PFOS exposure, peaking on day 21. In contrast, carbohydrate and lipid contents were reduced under PFOS relative to the control. PFOS exposure elevated glutathione-S-transferase activity, malondialdehyde, and hydrogen peroxide levels, whereas peroxidase activity was reduced. The phytoplankton biomass and lipids were positively associated, while oxidative stress markers were closely linked with high PFOS concentrations. Overall, these results highlight that PFOS exposure suppressed phytoplankton biomass, altered their community composition, and induced oxidative stress and metabolic shift at higher concentrations, highlighting its potential ecological risk in freshwater systems.

Effect of paraquat on the growth, antioxidant response and allelopathic interaction between Chlorella vulgaris and Selenastrum capricornutum - Yusuf Ibrahim Okpanachi; Suleiman Dauda; Onaji Onma Maria; Zainab Mohammed Tahiru; Yusuf Ishaku; Osagie Ekhator; Mathias Ahii Chia (Journal of Applied Phycology, 2026)

Impact of cylindrospermopsin-contaminated irrigation water on gas exchange and antioxidative mechanisms in lettuce and arugula - Micheline Kézia Cordeiro-Araújo; Mathias Ahii Chia; Adriana Sturion Lorenzi; Regina Anya Otogo; Suleiman Dauda; Maria Onma Onaji; Maria do Carmo Bittencourt-Oliveira (Journal of Applied Phycology, 2025)

The impact of the herbicide paraquat on the interaction between a macrophyte (Lemna minor) and two species of cyanobacteria (Microcystis aeruginosa and Microcystis flos-aquae) - Suleiman Dauda; Ejiroghene Ebelechukwu Uyovbisere; Adriana Sturion Lorenzi; Zainab Abdullahi Ibrahim; Sadiya Awala Samuel; Ibrahim Madu Katsallah Gadzama; Mathias Ahii Chia (Aquatic Ecology, 2025)

Allelopathic interactions between Lemna minor and Microcystis aeruginosa are influenced by the antimalarial drug lumefantrine - Suleiman Dauda; Ejiroghene Ebelechukwu Uyovbisere; Abdullahi Bala Alhassan; Ramatu Idris Sha’aba; Ibrahim Madu Katsallah Gadzama; Maria Onma Onaji; Mathias Ahii Chia (Aquatic Botany, 2024)

Nitrogen forms and concentration influence the impact of titanium dioxide nanoparticles on the biomass and antioxidant enzyme activities of Microcystis aeruginosa - Sadiya Awala Samuel; Mathias Ahii Chia; Waetsi Nya Yusufu; Suleiman Dauda; Wisdom Sohunago Japhet; James Dama Habila (Archives of Microbiology, 2023)

Environmentally relevant copper concentrations stimulate photosynthesis in Monoraphidium sp. - Suleiman Dauda; Ana Teresa Lombardi (Photosynthesis Research, 2023)

Combined nanoTiO2 and nitrogen effects on phytoplankton: a mesocosm approach - Suleiman Dauda; Ayene Martha Gabriel; Onozasi Firdaws Idris; Mathias Ahii Chia (Journal of Applied Phycology, 2020)